2017
DOI: 10.1590/1807-3107bor-2017.vol31.0031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of addition of [2-(methacryloyloxy)ethyl]trimethylammonium chloride to an experimental adhesive

Abstract: Influence of addition of [2-(methacryloyloxy)ethyl] trimethylammonium chloride to an experimental adhesiveAbstract: The aim of this study was to develop an experimental adhesive with addition of [2-(methacryloyloxy)ethyl]trimethylammonium chloride (METAC) and to evaluate its mechanical and biological properties and its in vitro antibacterial activity. An experimental adhesive resin was formulated with Bis-GMA, TEGDMA, and HEMA. The antibacterial monomer was added at concentrations of 1%, 2.5%, and 5% (METAC gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Methacrylate quaternary ammonium monomers (MQAM) chemically immobilized into the polymeric matrix have been used as a promising method to inhibit bacterial growth at resin composite surfaces. It is claimed that the great advantage of this approach is that the bioactive agent is not released from the matrix, which could contribute to the maintenance of the composites’ properties 8 . However, previous reports have shown that depending on the functionality and the concentration in which they are immobilized into the organic matrix, MQAMs can also reduce the mechanical properties 19 , and increase the water sorption of the composites 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Methacrylate quaternary ammonium monomers (MQAM) chemically immobilized into the polymeric matrix have been used as a promising method to inhibit bacterial growth at resin composite surfaces. It is claimed that the great advantage of this approach is that the bioactive agent is not released from the matrix, which could contribute to the maintenance of the composites’ properties 8 . However, previous reports have shown that depending on the functionality and the concentration in which they are immobilized into the organic matrix, MQAMs can also reduce the mechanical properties 19 , and increase the water sorption of the composites 4 .…”
Section: Introductionmentioning
confidence: 99%
“…37,38 The basic components of the adhesive system are: conditioning agent, primer and adhesive, in addition to photo initiators, polymerization inhibitors, and inorganic fillers. 33 They can also be modified with antimicrobial agents, [1][2][3][4][5][6][7][8][9][10][11][12][15][16][17][18][19][20]22,24,26,[28][29][30][31][39][40][41][42][43][44] mineralizing agents, 2,3,16,22,26,30,45 protein repellent, 2 inhibitors of metalloproteinases, 6,46,47 and even inti-inflammatory agents. 5 The understanding of the function of each system component and their careful use, respecting their indications, will be essential for adhesion success.…”
Section: Reviewmentioning
confidence: 99%
“…9,52 Many researchers develop new antimicrobial adhesives, or modify the materials available in the market with the addition of antimicrobial agents as a resort to secondary caries inhibiting mechanisms. [1][2][3][4][5][6][7][8][9][10][11][12][15][16][17][18][19][20]22,24,26,[28][29][30][31][39][40][41][42][43][44] Thus, the addition of benefit with potential to increase restoration longevity is desired. 16,52 In this context, nanotechnology has been used in caries prevention.…”
Section: Reviewmentioning
confidence: 99%
“…EFEITO ANTIMICROBIANODentre as técnicas utilizadas para avaliar o efeito antimicrobiano, os métodos de cultura mais difundidos são o ágar disco difusão, que mensura o diâmetro do halo de inibição promovida pelo antibacteriano(6,24,26,35,36,59,61); mínima concentração inibitória (MCI) e mínima concentração bactericida (MCB), que representam a quantidade de material (µg/ml) necessária para inibir o crescimento ou matar os microrganismos(26,51,69); contagem de unidades formadoras de colônias (UFC), contabiliza as colônias bacterianas formadas em placas de ágar(3,8,17, 23,24,26,27,34,36,40,41,45,46,48,59,61,(70)(71)(72)(73)(74)(75); 3-(brometo de 4,5-dimetiltiazol-2-yl)-2,5-difeniltetrazolio (MTT), mensura a atividade metabólica de bactérias pela absorbância do meio de cultivo(3, 8, 12, 23, 24, 26-28, 34, 41, 47, 48, 60); produção de ácido lático, que contabiliza a concentração de lactato produzido pelo biofilme(3,8, 12, 23, 24, 26-28, 34, 36, 46, 47); ensaio live/dead, demonstra qualitativamente as células bacterianas com a membrana comprometida, as quais são pigmentadas de vermelho, mediante atuação do corante propídio iodo, e as células bacterianas com membrana intacta coradas de verde pelo syto 9(3-6, 8, 10, 12, 23, 24, 26-28, 34-36, 41, 45-48, 61); 2,3-bis(2-metoxi-4-nitro-5-sulfofenil)-5-[(fenilamino)carbonil]-2Htetrazoliohidróxido (XTT), que semelhantemente ao MTT mensura a atividade mitocondrial por medida colorimétrica(6, 10); microscopia eletrônica de varredura (MEV), para análise morfológica do biofilme ou de sua adesão em determinada superfície(76). Além dos métodos de cultura previamente citados, existem os métodos moleculares como a reação em cadeia da polimerase (PCR), que detecta a presença ou ausência de determinado gene(77); a...…”
unclassified
“…5,24,28,35,60,61,69,71,72) ou de biofilme(3, 4, 8, 10, 12, 17, 23, 24, 26-28, 34, 36, 40, 41, 45-48, 59, 61, 75).Os métodos de cultura têm a desvantagem de serem incapazes de detectar bactérias viáveis mas não cultiváveis (VBNC), as que requerem condições especiais de cultivo, ou aquelas mortas(77,83), além disso, são trabalhosos, caros, e subestimam o número de células(43,77). Dentre os métodos moleculares, o mais lavrado é o qPCR, pois é capaz de quantificar a população de uma amostra, porém, tem como desvantagem a inabilidade de distinguir as bactérias vivas das mortas, o que superestima a contagem destes microorganismos(43,83,84).…”
unclassified